Tarifeinheit versus Tarifpluralität: Konfliktintensität von Verhandlungen - Hagen Lesch (Wirtschaftsdienst, 2013)
Eine Auswertung von Tarifkonflikten in Deutschland zeigt, dass Spartengewerkschaften eine hohe Konfliktbereitschaft aufweisen. Treten mehrere konfliktfreudige Gewerkschaften bei einem Arbeitgeber in Konkurrenz, kumulieren sich die Konflikthandlungen. Im Extremfall gerät ein Arbeitgeber von einer Tarifauseinandersetzung in die nächste. Der Gesetzgeber kann diese Folge von Tarifpluralität begrenzen, indem er die Tarifeinheit wiederherstellt. – – In some industries, wage negotiations are conducted not only by labour unions covering the whole sector but also by craft unions representing single occupations. A comprehensive evaluation of wage disputes in Germany shows that craft unions are especially confrontational. Particular problems arise if several confl ict-prone unions representing employees of the same company enter into competition with each other. The cumulative effects of such a situation can undermine the legal ban on industrial action while a collective wage agreement is in force. This damage could be limited by legislation regulating competition among trade unions and restoring exclusivity for wage agreements at the plant level (one company = one agreement).
Keywords: J50; J51; J52; 330; Gewerkschaft; Tarifverhandlungen; Deutschland